Connection capacity of the transition zone in steel-concrete hybrid beam = Nośność połączeń w strefie przejściowej w stalowo-betonowych belkach hybrydowych - Kozioł, Piotr; Kożuch, Maciej; Lorenc, Wojciech; Rowiński, Sławomir (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The problem of transition zone of structural steel element connected to concrete is discussed in the following paper. This zone may be located for instance in specific bridge composite girder. In such case the composite beam passes smoothly into concrete beam. Because of several dowels usage in the transition zone, the problem of uneven force distribution were discussed through analogy to bolted and welded connections.
Keywords: transition zone; hybrid beam; perfobond connectors; destructive tests; composite structures; strefa przejściowa; belka hybrydowa; łączniki perfobond; badania niszczące; konstrukcje zespolone